Improving Public Service Efficiency through the Development of the SPINTAR Information System at the Central Statistics Agency of Sukabumi City - Muhamad Satria Satria; Imam Sanjaya (LPPM STMIK Mardira Indonesia, 2026)
This research was conducted as part of an internship program organized by Nusa Putra University and held at the Central Statistics Agency in Sukabumi City. The main problems identified were the suboptimal public service process, which still relied on manual procedures and the lack of system integration. This situation resulted in low service efficiency and delays in delivering information to the public. Therefore, this project aimed to improve the quality and effectiveness of services through the development of a web-based information system. The method used combined a user-needs-based approach with the Rapid Application Development (RAD) model. Data collection was conducted through direct observation and interviews to identify specific system requirements. The system was then designed, developed, and tested in stages to ensure its functionality met user needs. The result of this project was the SPINTAR information system, which provides a more structured, faster, and more accessible service mechanism. This system also improved data management and strengthened interaction between users and agencies. In conclusion, the implementation of the SPINTAR system successfully increased the efficiency of public services while supporting the digital transformation process at Central Statistics Agency in Sukabumi City. In addition, this activity provides practical experience for students in applying academic knowledge directly in a real work environment.